Pengaruh Lingkungan Kerja Dan Displin Kerja Terhadap Kinerja Pegawai Pada Kantor Pemerintahan Daerah Kabupaten Banyuwangi - Huda, Lucky Miftakhul; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to find out how the work environment and work discipline influence employee performance at the Banyuwangi Regency Regional Government Office. The approach in this research is a quantitative approach. The population used in this research were Banyuwangi Regency Regional Government employees. Meanwhile, the sample used in the research was 111 employees at the Banyuwangi Regency Regional Government Office. The data collection technique used in this research used a questionnaire. And the analytical method used in this research is multiple linear regression using SPSS 20 for Windows. The results of this research show that the work environment partially has no significant effect on employee performance, work discipline partially has a significant effect on employee performance, work environment and work discipline simultaneously have a significant effect on employee performance. Keywords: Work environment, work discipline, employee performance